2002
DOI: 10.1097/00002826-200203000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Successful Use of Donepezil for the Treatment of Psychotic Symptoms in Patients With Parkinson's Disease

Abstract: The risk of psychosis among patients with Parkinson's disease (PD) is high, and the management of these patients remains a substantial problem for physicians. Atypical antipsychotics, despite their advantages over conventional antipsychotics, can cause different side effects and deterioration of PD. Several reports have suggested that donepezil can be helpful in the treatment of psychotic conditions in patients with dementia with Lewy bodies and Alzheimer's disease. This report presents the results of prelimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
62
1
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(73 citation statements)
references
References 33 publications
4
62
1
4
Order By: Relevance
“…Donepezil has been shown to improve cognition for up to 52 weeks in longterm treatment of NCDLB patients, without increasing the risk of Parkinsonian features or other clinically significant safety events [76,77]. Donepezil has also been shown to reduce Lewy pathology cholinergic impairment including hallucinations and delusions and psychotic symptoms in PD patients, without apparent side effects or exacerbation of Parkinsonian symptoms [78][79]. Although an early study suggested that treatment of NCDLB with Donepezil was sometimes associated with an increase in Parkinsonian features, a Cochrane database systematic review of previous research using cholinergic agonists to treat PD & NCDLB found that Donepezil produced consistent reduction in neurocognitive symptoms without exacerbation of Parkinsonian features or other side effects [87,88].…”
Section: Symptom Treatment Of Cholinergic Lewy Pathologymentioning
confidence: 99%
See 1 more Smart Citation
“…Donepezil has been shown to improve cognition for up to 52 weeks in longterm treatment of NCDLB patients, without increasing the risk of Parkinsonian features or other clinically significant safety events [76,77]. Donepezil has also been shown to reduce Lewy pathology cholinergic impairment including hallucinations and delusions and psychotic symptoms in PD patients, without apparent side effects or exacerbation of Parkinsonian symptoms [78][79]. Although an early study suggested that treatment of NCDLB with Donepezil was sometimes associated with an increase in Parkinsonian features, a Cochrane database systematic review of previous research using cholinergic agonists to treat PD & NCDLB found that Donepezil produced consistent reduction in neurocognitive symptoms without exacerbation of Parkinsonian features or other side effects [87,88].…”
Section: Symptom Treatment Of Cholinergic Lewy Pathologymentioning
confidence: 99%
“…Based on researchdemonstrating Donepezil's efficacy in treating cholinergic impairment in patients with PD and NCDLB, and its effectiveness in reducing constipation and increasing bowel motility in non geriatric patients [73][74][75][76][77][78][79][88][89][90]93,94]. Donepezil has been used specifically to treatconstipation in PD and NCDLB patients, with consequent significant reduction of the symptom of constipation, without exacerbation or instigation of other symptoms [39].…”
Section: Symptom Treatment Of Cholinergic Lewy Pathology In the Ensmentioning
confidence: 99%
“…Cholinesterase inhibitors, including donepezil [53][54][55] and rivastigmine, 56 have been shown to improve symptoms of PDP in case reports and small openlabel studies; however, larger controlled studies are necessary to determine if these agents may be beneficial for PDP. A case report has suggested a potential benefit of mirtazapine for PDP; 57 however, antidepressants have been shown to induce or exacerbate psychotic symptoms, [58][59] so further research is necessary to determine if this is a reasonable treatment option for PDP.…”
Section: Other Pharmacologic Approachesmentioning
confidence: 99%
“…Since the clinical manifestations of DLB and PDP seem very close, if not identical, other than the obvious difference that many of the PDP patients are not demented, it would seem reasonable that they may also be helpful in PDP. The effects of CEI in PDP have been the subject of only a few open label trials [105][106][107][108][109], showing good tolerance and some benefit. One problem with such an approach is the long lag time between drug initiation and clinical response.…”
Section: Managementmentioning
confidence: 99%